The Use of Discourse Markers As Cohesive Devices in Donald Trump’s Commencement Speech at University of Liberty - Rahayu, Sabti; Ekawati, Rosyida (Alphabet, 2025)
This study is focused on the use of discourse markers by Donald Trump in his speech entitled Never, Ever Give Up. The purposes of this study are to find out the types of discourse markers used during the speech and the function by using Fraser's theory (2009) to analyze the types of discourse markers and Schiffrin's theory (1987) to analyze their function. In this study, the data used are utterances uttered by Donald Trump during his speech which contain discourse markers. Therefore, the writer used descriptive qualitative research method to analyze this topic. The writer used data analysis technique from Miles, Huberman and Saldana (2014). As a result, the writer found all categories of discourse markers used by Donald Trump during his speech. There are 22 data included in the discourse markers. Among them are 2 contrastive discourse markers, 10 elaborative discourse markers, 2 inferential discourse markers, and 8 temporal discourse markers. Based on the functions, the writer found that from 6 functions of discourse markers, there was 1 function which not found in the data namely marker of information management.